The Effect of Slaughter Age on Meat Quality of Male Kids of the Polish Carpathian Native Goat Breed - Aldona Kawęcka; Marta Pasternak (Animals, 2022)
The native breed of Carpathian goats, once abundant in the foothills of Poland, practically died out and was replaced by other, more efficient breeds. As a result of reintroduction activities and its inclusion in the genetic resources program, breeding was restored. The dynamically developing population of Carpathian goats is an extremely valuable element of biodiversity and a potential for the development of the market for its products, including goat meat. The study aimed to compare the carcass measurements and the quality and composition of meat from male kids of the Polish Carpathian native goat breed slaughtered at the ages of 9 and 12 months. Muscle samples were taken from the leg (m. biceps femoris) to determine the meat chemical composition and physicochemical and sensory parameters, as well as the fatty acid profile. The dressing percentage was higher in older kids (41.27%) than in younger ones (37.89%), as well as final weight and cold carcass weight. The weight of valuable cuts such as the loin and leg differed between groups, and it was significantly higher in 1-year-old kids. No differences were found in basic ingredients, such as moisture, protein, ash and vitamins A and E, depending on the kids’ slaughter age. The fat concentration was significantly higher in the group of younger kids. Significant differences occurred in relation to the physicochemical parameters, fatty acid profile and organoleptic properties. The findings demonstrated that the meat of older kids was characterised by darker colour and a slightly higher pH, and it contained a higher concentration of hypocholesterolemic fatty acids (DFA) and a more favourable DFA/OFA ratio. Roasted meat from the Carpathian kids scored high marks in the organoleptic assessment and the meat obtained from older animals was rated higher.